KNOWLEDGE MANAGEMENT AS THE FOUNDATION OF BUSINESS PROCESS MANAGEMENT – AN OVERVIEW OF THE RELEVANT LITERATURE - Petrović, Marijana; Rajin, Danica; Stojiljković, Aleksandra (Journal of process management and new technologies, 2019)
The aim of this paper is to highlight the importance knowledge management and business processes management has in the modern economy. The paper reflects on the impact of knowledge management on business processes and on the improvement of the management thereof, on the basis of the relevant literature. The related research shows a mutual connection between these two concepts and points to the potential benefits of their successful integration. This paper is a framework overview of all the positive effects of knowledge management on business process management in the organization, which allows for better understanding and use of knowledge for more effective business process management.